Transnational knowledge in volunteering for development – A postcolonial approach to weltwärts. Issue 1 (2nd January 2018) - Haas, Benjamin; Repenning, Alexander
Abstract: International volunteering for development programs (V4D) are on the rise. Weltwärts is by far the largest program in Germany, with thousands of participants. These programs constitute transnational arenas of knowledge production, as their networks transcend nation-states boundaries and produce rules, ideas, and knowledge that travel through these networks. V4D programs claim to contribute to knowledge production. In this article, we examine how and where knowledge is created, shaped, and contested within the weltwärts program. To do so, we analyze documents, secondary data, two qualitative case studies, and informal interviews with stakeholders. We draw on postcolonial theory and the literature on transnational knowledge in order to analyze possibilities for transnational knowledge production, as well as its challenges and barriers. We argue that unequal power relations lead to structural underrepresentation of perspectives and knowledge of stakeholders from the global South, despite the good will of numerous stakeholders in the North. However, we also note that stakeholders in the South have started to claim such opportunities for participation and even organize their own spaces of knowledge production and networking. We conclude that developing transnational understandings of concepts like development, decision-making processes in transnational settings must critically reflect upon and overcome postcolonial power structures.